Assessing investment sector in the context of overall default profile of First Security Islami Bank Ltd., Banani Branch - Islam, Nusrat (BRAC University, 2018)
This internship report is submitted in a partial fulfilment of the requirements for the degree of Masters of Business Administration, 2017.